Algorithm's Cradle: Commemorating al-Khwarizmi in the Soviet history of mathematics and Cold War computer science - TATARCHENKO, Ksenia (Institutional Knowledge at Singapore Management University, 2023)
This chapter investigates the origin narratives and commemoration practices that came hand in hand with the growing cultural authority of the algorithm after World War II, culminating in celebrations in honor of the 1,200th anniversary of the medieval scholar Abu MODIFIER LETTER LEFT HALF RINGAdallah Muhammad Ibn Musa al-Khwarizmi. I first show how al-Khwarizmi's legacy was claimed by Soviet historians of mathematics aiming to construct a history inspired by dialectical materialism, a goal that eventually led to arguments about the distinct, algorithmic character of mathematics in the East. Next, I study how these ideas were appropriated by the international community of computer scientists in search of the origins for their discipline. The late-Soviet coupling of commemoration rituals with programming literacy campaigns evolved into an enduring cultural reference shared across post-Soviet spaces. Such alternative symbolic lives of the algorithm suggest a need to suspend assumptions of universality in historicizing the global modalities of algorithmic culture.